Diferenciação morfotípica de machos de camarão de água doce Macrobrachium amazonicum (Heller, 1862) (Crustacea, Decapoda, Palaemonidae) - Moraes-Riodades, Patrícia Maria Contente [UNESP] (2002)
The aim of this paper was to investigate the morphotypic differentiation of Macrobrachium amazonicum male. A key for identification of these morphotypes was provided using observations on color and spination of chelipeds supplemented by relative growth techniques. Prawns were taken from nine earthen ponds at Jaboticabal, São Paulo, Brazil. Total length, post-orbital length and the length of carapace, chelipeds and all limb joints were measured on the right second pereiopod with a vernier caliper. Four distinct morphotypes were identified, Translucent Claw (TC), Cinnamon Claw (CC), Green Claw (GC) and Green Claw apostrophe (GC' ). They differ by chelipeds morphology and several morphometric relationships. TC prawns are small in size and present chelipeds translucent with tubercles or spines, which point distally at an angle £ 60º. CC males are similar to TC in size and spination, but present cinnamon chelipeds. GC and GC' are large prawns with long dark green chelipeds provided with long and robust spines, which point distally at an angle ranging between 60º and 90º. They differ only by chelipeds proportion. GC cheliped length overtake post-orbital length while the opposite occurs in GC' males. Recognition of morphotypes will be useful for future biology and culture works aiming increase pond production of M. amazonicum